Evaluating the Effectiveness of African School of Hypertension for Non-Physician Health Workers, a Qualitative Study: QuASH Hypertension Study - Godsent C. Isiguzo; Oluseyi A. Adejumo; Ifeanyi E. Nwude; Uzochukwu M. Amaechi; Ayodele Y. Ayoola; Manmak H. Mamven; Reuben K. Mutagaywa; Ayodipupo S. Oguntade; Kelechi G. Isiguzo; Abiodun M. Adeoye; Beheiry M. Hind; Alfred Doku; et al. (Ubiquity Press, 2024)
Background: The implementation of task sharing and shifting (TSTS) policy as a way of addressing the shortage of physicians and reducing the burden of hypertension in Africa birthed the idea of the African School of Hypertension (ASH). The ASH is saddled with the responsibility of training non-physician health workers across Africa continent in the management of uncomplicated hypertension. Aim: To get feedback from some faculty members and students who participated in the first ASH programme. Methods: This was a cross-sectional exploratory qualitative study conducted among eight students and eight faculty members. Feedback from the program was obtained by conducting in-depth interviews centred on description of course content; expectations and knowledge acquired from ASH; level of interaction between students and faculty members; challenges faced during the ASH; level of implementation of acquired training; and suggestions to improve subsequent ASH programs Results: The course content of the ASH was described as simple, appropriate and adequate while interaction between students and faculty members were highly cordial and engaging. New knowledge about hypertension management was acquired by the students with different levels of implementation post-graduation. Some identified challenges with the ASH program were poor internet connectivity during lectures, non-uniformity of TSTS policies and hypertension management guidelines across Africa, technical problems with hypertension management app and low participation from other African countries apart from Nigeria. Some recommendations to improve ASH program were development of a uniform hypertension management guideline for Africans, wider publicity of the ASH, interpretation of lectures into French and Portuguese languages and improvement of internet connectivity. Conclusion: The ASH programme has largely achieved its objectives with the very encouraging feedback received from both faculty members and the students. Steps should be taken to address the identified challenges and implement the suggested recommendations in subsequent ASH program to sustain this success.